Academic approaches related to palliative care in higher education: Exploratory study (Research, Society and Development, 2020)
The theme related to palliative care (PC) should be inserted in the curriculum of undergraduate education, thus favoring the promotion of real knowledge practiced in the current health system. This study aimed to evaluate the pedagogical approaches related to PC used by professors of the physiotherapy course of a higher education institution. It is a descriptive, exploratory and quantitative / qualitative research carried out through a questionnaire composed of open and closed questions with 13 professors from the institution. In view of the results, it was observed that the theme of PC is not included in the menu and / or in the objectives of many subjects of the course, however, teachers insert this theme using some methodological approaches in classes, such as lectures, case studies and technical visits. Based on these findings, it is recommended that teachers make use of pedagogical strategies that make it possible to approach the subject of PC in the disciplines of undergraduate health courses.